2006
DOI: 10.2223/jped.1497
|View full text |Cite
|
Sign up to set email alerts
|

Immunizations: three centuries of success and ongoing challenges

Abstract: Como citar este artigo: Feijó RB, Sáfadi MA. Immunizations: three centuries of success and ongoing challenges. J Pediatr (Rio J). 2006;82(3 Suppl):S1-3. EDITORIAL0021-7557/06/82-03-Supl/S1 No início do século 17, a varíola era uma das doenças transmissíveis mais temíveis no mundo, atingindo, até a juventude, a maioria das pessoas e representando uma alta taxa de mortalidade. Lady Mary Montagu, esposa do embaixador inglês em Istambul, observou que a doença poderia ser evitada através de uma técnica utilizada pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 1 publication
0
9
0
7
Order By: Relevance
“…Edward Jenner was responsible for the records in the 18 th century. He observed that peasants were not affected by smallpox when in contact with infected cows, (1,2) which was recognized when the efficacy of the microorganism inoculation was verified in the immunological stimulation, with a lower number of people getting sick. (1) In Brazil, the first vaccination campaign, conceived by Osvaldo Cruz, took place in 1904 and focused on reducing smallpox morbidity and mortality.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…Edward Jenner was responsible for the records in the 18 th century. He observed that peasants were not affected by smallpox when in contact with infected cows, (1,2) which was recognized when the efficacy of the microorganism inoculation was verified in the immunological stimulation, with a lower number of people getting sick. (1) In Brazil, the first vaccination campaign, conceived by Osvaldo Cruz, took place in 1904 and focused on reducing smallpox morbidity and mortality.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…Brazil has performed very well with the Programa Nacional de Imunizaç ões as an integrated programme of the global immunization strategies of the World Health Organization (WHO), putting into practice routines, campaigns and mass vaccination with free vaccines [6]. Despite of its success, there are still ongoing challenges [7].…”
Section: Introductionmentioning
confidence: 99%
“…No início do século XVII, a varíola era uma das doenças transmissíveis mais temidas do mundo, por atingir pessoas de vários grupos sociais e etários e pela alta mortalidade. As primeiras técnicas de imunização contra a doença surgiram a partir de estudos com camponeses em contato com vacas infectadas por varíola bovina (FEIJÓ;SÁFADI, 2006). A vacina da raiva, uma doença incurável, somente foi desenvolvida no século XIX, por Louis Paster (PLOTKIN; PLOTKIN, 2004).…”
Section: Brasilunclassified
“…, dos casos sorotipados, 47,5% foram causados por sorotipos incluídos na vacina e foi observado aumento do número de casos no período pós-vacina de outros sorotipos não incluídos na PCV10 (HIROSE; MALUF; RODRIGUES, 2015).Com relação a Doença Meningocócica (DM), é problema de saúde pública em todo o mundo, ainda no século XXI, tanto por seu caráter epidêmico quanto por sua evolução rápida e elevada letalidade(SÁFADI;BARROS, 2006). A Neisseria meningitis é um diplococo gram-negativo capsular, classificado em 13 sorogrupos.…”
unclassified